Prognostic evaluation of the norepinephrine equivalent score and the vasoactive-inotropic score in patients with sepsis and septic shock: a retrospective cohort study - Li, Wenzhe; Wang, Yi; Abuduaini, Buzukela; Li, Xiang; Pan, Pengfei; Cui, Jian; Yu, Xiangyou (Frontiers in Cardiovascular Medicine, 2024)
Background This study investigated the association between vasoactive medication exposure and mortality risk in patients with sepsis using the norepinephrine equivalent (NEE) score and vasoactive-inotropic score (VIS). Methods This retrospective cohort study included adult patients with sepsis requiring vasoactive agents. The data were extracted from the Medical Information Mart for Intensive Care IV database. The primary outcome was 28-day mortality. Multivariate Cox regression was used to elucidate the relationship between vasoactive medication exposure and 28-day mortality, as quantified by the VIS and NEE score. Hazard ratios with 95% confidence intervals (CI) for 28-day mortality were generated, and forest plots were constructed to present the results of univariate and multivariate analyses. The Kaplan–Meier method was used to analyze the cumulative incidence of 28-day mortality. A nomogram was constructed to predict the prognosis of patients with sepsis. Results The present study encompassed 9,032 patients diagnosed with sepsis who received vasoactive therapy, of which 4,229 patients were further analyzed at the second hour after the onset of sepsis. Distinct variations in demographic data were observed between survivors (n = 3,265, 77.21%) and non-survivors (n = 964, 22.79%). Multivariate analysis indicated that several factors, including VIS >15.04 (p = 0.001), NEE >0.10 (p < 0.001), heart rate (p = 0.045), mean arterial pressure (p = 0.009), respiratory rate (p < 0.001), oxygen saturation (p < 0.001), blood urea nitrogen (BUN) (p = 0.001), and the Acute Physiology and Chronic Health Evaluation II (p < 0.001), were significantly associated with 28-day mortality in the patients with sepsis. The NEE score, respiratory rate, oxygen saturation, and BUN were incorporated into the nomogram model with a concordance index of 0.779 and an area under the curve of 0.802 (95% CI 0.787–0.818). Conclusion We found that the VIS and NEE score had favorable values for predicting mortality risk in patients with sepsis in the intensive care units. The VIS and NEE score in the second hour after sepsis onset were independently associated with 28-day mortality in patients with sepsis.